Physiology of accidental hypothermia in the mountains: a forgotten story. Issue 6 (9th December 2003) - Ainslie, P N; Reilly, T
Abstract : Hypothermia is a serious condition, often with fatal consequences. The physiology and mechanisms of hypothermia in mountainous areas are discussed. It is as important to facilitate heat loss, especially during periods of high exertion, as it is to maintain heat production and preserve insulation. This can be partly achieved by clothing adjustments.